Reasons for the formation of historical Kyiv as a sacral center - Bachynska, Olha (КНУБА, 2018)
Kyiv has become a sacred city due to several factors. History has influenced the significant development of the sacred function.
Keywords: Kyiv; buildings; history; temples; dominant.; 7611.46